2002
DOI: 10.1021/jf0109165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Extent of Hemoglobin Hydrolysis on the Digestive Absorption of Heme Iron. An In Vitro Study

Abstract: This study was designed to assess the interactions of heme with peptides produced by enzyme hydrolysis of hemoglobin, and their relationship with heme iron absorption. Bovine hemoglobin was hydrolyzed by pepsin or by subtilisin, which differ in their hydrolysis processes. The hydrolysis rate ranged from 0 (native hemoglobin) to 15%. Heme solubility and heme-peptides interactions were compared to iron absorption by the Ussing chamber model, at intestinal pH (7.5). Increasing hemoglobin hydrolysis enhanced iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 27 publications
2
37
1
2
Order By: Relevance
“…The hemeiron polypeptide product in the present study contained globinderived peptides, but no intact globin. Purified heme is poorly absorbed because of polymerization at low gastric pH; peptides produced by digestion of globin prevent heme polymerization and enhance absorption of the intact metalloporphyrin molecule (47)(48)(49). Although the present results suggest that supplementation with 5 mg iron in this heme form may increase body iron about half as effectively as 50 mg iron from ferrous sulfate, this was not sufficient to distinguish it from the placebo.…”
Section: Discussioncontrasting
confidence: 72%
“…The hemeiron polypeptide product in the present study contained globinderived peptides, but no intact globin. Purified heme is poorly absorbed because of polymerization at low gastric pH; peptides produced by digestion of globin prevent heme polymerization and enhance absorption of the intact metalloporphyrin molecule (47)(48)(49). Although the present results suggest that supplementation with 5 mg iron in this heme form may increase body iron about half as effectively as 50 mg iron from ferrous sulfate, this was not sufficient to distinguish it from the placebo.…”
Section: Discussioncontrasting
confidence: 72%
“…Under these conditions, heme Fe from a digest is absorbed better than intact hemoglobin. Vaghefi et al [20] showed the extent to which hemoglobin hydrolysis affects the absorption of heme. Hb hydrolysis is an enzymatic process that occurs in the intestinal lumen, and therefore, imitating this digestion will give a better model for heme uptake by cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the different ingredients utilized in the formulation of the hemoglobin-fortified cookies may have masked the characteristic flavor of hemoglobin, rendering it imperceptible in this case. Some skeptics have opined that it is impractical to use hemoglobin as an iron supplement because it is low in iron (0.35%) [107], poorly soluble at low gastric pH [107], and its absorption is usually less than iron absorption from muscle [108,109]. Heme iron polypeptide (HIP), a soluble heme moiety with an attached polypeptide obtained from the enzymatic digestion of bovine or porcine hemoglobin has been developed to overcome these concerns.…”
Section: Iron Supplementmentioning
confidence: 99%
“…Heme iron polypeptide (HIP), a soluble heme moiety with an attached polypeptide obtained from the enzymatic digestion of bovine or porcine hemoglobin has been developed to overcome these concerns. The hydrolysis action enhances iron absorption by preventing the formation of large insoluble heme polymers [107]. Examples of commercially available HIP products are Proferrin® (Colorado Biolabs Inc., Frederick, CO) and Aprofer 1000® (APC Europe, S.A., Barcelona, Spain).…”
Section: Iron Supplementmentioning
confidence: 99%